Incidence and Predictive Factors of Postprandial Hyperinsulinemic Hypoglycemia After Roux-en-Y Gastric Bypass: A Five year Longitudinal Study. Issue 5 (November 2016) - Raverdy, Violeta; Baud, Gregory; Pigeyre, Marie; Verkindt, Helene; Torres, Fanelly; Preda, Cristian; Thuillier, Dorothee; Gélé, Patrick; Vantyghem, Marie-Christine; Caiazzo, Robert; Pattou, François
Abstract : Background: Postprandial hyperinsulinemic hypoglycemia (PHH) is often reported after Roux-en-Y gastric bypass (RYGB). In the absence of a prospective study, the clinical and biological determinants of PHH remain unclear. Objective: To determine the incidence and predictive factors of PHH after RYGB. Methods: Participants were 957 RYGB patients enrolled in an ongoing longitudinal cohort study. We analyzed the results of an oral glucose tolerance test (OGTT) routinely performed before surgery and 1 and/or 5 years after. PHH was defined as blood glucose < 50 mg/dL AND plasma insulin > 3 mU/L at 120 minutes post glucose challenge. Validated indices of insulin sensitivity (Matsuda index), beta-cell function (Insulinogenic index), and beta-cell mass (fasting C-peptide: glucose ratio) were calculated, from glucose, insulin, and c-peptide values measured during OGTT. Results: OGTT results were available in all patients at baseline, in 85.6% at 12 months and 52.8% at 60 months. The incidence of PHH was 0.5% at baseline, 9.1% * and 7.9%* at 12 months and 60 months following RYGB (*: P < 0.001). In multivariate logistic regression analysis, PHH after RYGB was independently associated with lower age ( P = 0.005), greater weight loss ( P = 0.031), as well as higher beta-cell function ( P = 0.002) and insulin sensitivity ( P < 0.001), but not with beta-cell mass ( P = 0.381). A preoperative elevated beta-cell function was an independent predictor of PHH after RYGB (receiver operating characteristics curve area under the curve 0.68, P = 0.04). Conclusions: : The incidence of PHH significantly increased after RYGB but remained stable between 1 and 5 years. The estimation of beta-cell function with an OGTT before surgery can identify patients at risk for developing PHH after RYGB.